VISITOR PERCEPTION ON THE ASPECTS THAT CREATES THE KYA-KYA SENSE OF PLACE: THE PHYSICAL EVIDENCES - Gracia, Angelique; Davina, Ardelia; Natalie, Cindy; Tobing, Jeremy; Indrasakti, Marsha; Udayana, Michael; Goeinawan, Winston (Aksen : Journal of Design and Creative Industry, 2024)
Kya-Kya is a Chinatown area, which is part of the old city of Surabaya. This place has become a culinary tourism destination and feasts visitors’ eyes on architecture that is viscous with oriental elements in its buildings. Various foods and beverages are available to welcome visitors, with seating areas decorated with round tables and chairs. Interestingly, this area provides opportunities for researchers who aim to define physical evidence of the tourism area, which is a tactic of the marketing mix. Physical evidence is one of the seven marketing mixes, which are product, price, place, promotion, people, and process. Good physical evidence is expected to increase the intention of repeat visits and word of mouth. This study used a quantitative method. Data collection was based on numerical data and 65 respondents’ data, and a direct visit to the Kya-Kya area was performed to observe the surrounding atmosphere. The results of the study revealed that physical evidence that has been proven to make a contribution was Chinatown architecture, buying and selling activities, and interiority in the Kya-Kya area. Keywords: Architecture, Interior, Physical Evidence, Sense of Place, Site